The Influence of Learning Organization and Transformational Leadership on Employee Performance: Unveiling the Role of Job Satisfaction at UMARA Foundation - Rusilowati, Umi; B., Hamsinah; Taryo, Taswanda; Sholihin, Dwi Rahmad (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research aims to analyze the influence of learning organizations and transformational leadership on employee performance through job satisfaction at the UMARA Foundation. The approach used is quantitative with census techniques, where all 300 employees were used as respondents. Data was collected using a questionnaire with a Likert scale, which was then analyzed using Stata MP17 software. Based on the results of the analysis, it can be concluded that learning organizations and transformational leadership have a significant positive influence on job satisfaction, which shows that learning in organizations and transformational leadership can increase employee job satisfaction. Meanwhile, although learning organizations have a significant effect on employee performance through job satisfaction, transformational leadership does not show a significant effect on employee performance. In addition, job satisfaction functions as a significant mediator in the relationship between learning organization and transformational leadership on employee performance. These results indicate that to improve employee performance, companies need to focus on efforts to increase employee job satisfaction, which in turn can encourage better performance. Overall, this research emphasizes the important role of learning organizations and transformational leadership in improving employee performance through increasing job satisfaction. The suggestion that must be made is that the UMARA foundation needs to strive to improve aspects related to job satisfaction, such as, satisfaction with rewards, promotion opportunities, relationships with superiors and co-workers.